Participação de proteínas ligantes de heparina na interação entre Toxoplasma gondii e as células hospedeiras - Bonilha, Martha Ribeiro (2003)
Toxoplasma gondii is able to invade virtually any nucleated cell, suggesting that this parasite may bind through a ubiquitous receptor. The aim of this study was to identify heparin—binding proteins involved in T. gondii adhesion to host cells, since heparin/heparan sulfate proteoglycans are putative receptors for the parasite. Tachyzoites from RH strain collected from mouse peritoneal exudate or HFF cells were extracted with 1% Triton—X- 100 at 37°C and the soluble fraction was applied onto a heparin afﬁnity column. Heparin ligands were eluted with NaCl and resolved by SDS-PAGE. Proteins ranging in weight from. 5-100kDa were identified and blotted onto a PVDF membrane. A polypeptide of approximately 5kDa was N-terminal sequenced, revealing 100% homology with mouse calgranulin A, a calcium—binding protein. This protein was not dislocated when parasites were washed with 1M NaCl before lysis, indicating a stable binding to the parasite surface. Our results demonstrated that T. gondii tachyzoites might adsorb host heparin-binding proteins, suggesting that the parasite may utilize such proteins, like calgranulin A, to facilitate adhesion and invasion of the host cells